2014
DOI: 10.1128/aac.02953-14
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Trough Plasma Ganciclovir Levels and Peripheral Blood Cytomegalovirus (CMV)-Specific CD8 + T Cells To Predict CMV DNAemia Clearance in Preemptively Treated Allogeneic Stem Cell Transplant Recipients

Abstract: It is uncertain whether monitoring plasma ganciclovir (GCV) levels is useful in predicting cytomegalovirus (CMV) DNAemia clearance in preemptively treated allogeneic stem cell transplant recipients. In this observational study, including 13 episodes of CMV DNAemia treated with intravenous (i.v.) GCV or oral valganciclovir, we showed that monitoring trough plasma GCV levels does not reliably predict response to therapy. Rather, immunological monitoring (pp65 and immediate-early [IE]-1-specific gamma interferon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
(29 reference statements)
4
19
0
Order By: Relevance
“…At present, GCV and ValGCV dosing decisions are not routinely informed by use of a therapeutic range. The target cut‐offs for C min vary across different laboratories and range between 0.06 and 2.5 μg/mL in human organ and tissue transplant studies . The dose‐dependent inhibition of human CMV replication by GCV has been established in vitro, with a reported 50% inhibitory concentration of 1.5 μg/mL …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, GCV and ValGCV dosing decisions are not routinely informed by use of a therapeutic range. The target cut‐offs for C min vary across different laboratories and range between 0.06 and 2.5 μg/mL in human organ and tissue transplant studies . The dose‐dependent inhibition of human CMV replication by GCV has been established in vitro, with a reported 50% inhibitory concentration of 1.5 μg/mL …”
Section: Discussionmentioning
confidence: 99%
“…25 Despite these reports, contrasting results were found in pharmacodynamic studies investigating the relationship between the therapeutic effect of different GCV blood concentrations. 23,[25][26][27][28] Consequently, there is currently no consensus regarding the use of clinical drug monitoring for GCV in SOT recipients, although given the low but significant numbers of transplant recipients failing therapy, the use of antiviral concentration monitoring needs to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…TDM facilitates optimal dosing of antivirals as therapeutic levels may vary depending upon renal function, particularly in the case of ganciclovir . Dose adjustment based on population pharmacokinetics Bayesian prediction model has been demonstrated to optimise exposure in solid organ transplantation, although a study of TDM in HSCT showed that immune status is more important than trough ganciclovir levels in predicting clearance of CMV during pre‐emptive therapy . TDM is not routinely available at present but can be performed in a research setting.…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…20 Dose adjustment based on population pharmacokinetics Bayesian prediction model has been demonstrated to optimise exposure in solid organ transplantation, 20 although a study of TDM in HSCT showed that immune status is more important than trough ganciclovir levels in predicting clearance of CMV during pre-emptive therapy. 21 TDM is not routinely available at present but can be performed in a research setting. Further research is warranted in HSCT recipients to optimise ganciclovir and valganciclovir dosage, and for use with novel antivirals where less is known about doseresponse relationships.…”
Section: Resistance Testingmentioning
confidence: 99%
“…It has been increasingly recognized that sequential immunological monitoring of CMV-specific T-cell immunity during episodes of active CMV infection may help to individually tailor the dosing and duration of antiviral therapy. This will perhaps result in shorter courses and thus less drug-related toxicity and a lower incidence of recurrent episodes of CMV replication [Sester et al, 2001;Gerna et al, 2006Gerna et al, , 2011Nebbia et al, 2008;Abate et al, 2010;Benmarzouk-Hidalgo et al, 2011;Solano et al, 2011;Lisboa et al, 2012;Gim enez et al, 2014b].…”
Section: In Transplant Patients: Unmet Needsmentioning
confidence: 99%